A MODERN TEACHER IN THE WORLD OF DIGITAL DIDACTICS AND DIGITAL EDUCATION (Universal International Scientific Journal, 2026)
This article examines the challenges and methods of teaching in the modern world, where the speed of information and diversity of communication channels have reached unprecedented levels, making speech culture issues particularly relevant. Linguists, psychologists, and sociologists are unanimous in their assessments of the current state of the speech environment, highlighting a number of alarming trends that affect both society as a whole and individuals.
Keywords: Digitalization, digital generation, digital didactics, digitalization of education, distance learning, online learning, development of speech culture and communication etiquette.